The Role of BAPPEDA In Formulating Planning and Budgeting in Intervening in Poverty Reduction - Dongi, Nur Annisa Lutaan; Sading, Yunus; Jokolelono, Eko; Jaya, Andi Herman; Tuty, Farida Milias (Manunggal Halim Jaya, 2024)
Various poverty reduction programs, especially in Central Sulawesi, have been implemented by the government, including in the socio-economic, health and education sectors. Mapping the poverty reduction program plan is needed to increase the effectiveness of each program implemented. The poverty reduction programs launched by the government have not been able to significantly reduce the poverty rate. In order to reduce poverty, it is necessary to take strategic, comprehensive and sustainable steps that can have an impact on reducing poverty. The purpose of this study is to see how the role of Bappeda in formulating planning and budgeting to reduce poverty in Central Sulawesi. The method used in this research is a descriptive qualitative method. The results of this study indicate that bappeda as a facilitator and the process of formulating planning and budgeting has carried out its duties as regulated by law. The Central Sulawesi BAPPEDA in formulating poverty reduction planning compiles the Annual Regional Development Plan in the form of the Regional Government Work Plan (RKPD) through the implementation of absorption and aspiration gathering in the form of a Development Planning Consultation (Musrenbang) forum. The results of the Musrenbang contain a budget framework for activity plans that need to be funded by funding sources, be it the Regency APBD, Provincial APBD, APBN or other sources of funds. After the musrenbang, the RKPD is determined, which is then contained in the PERDA.